STRATEGI MENINGKATKAN DAYA SAING USAHA PT.X MELALUI RENCANA PEMBANGUNAN UNIT STONE CRUSHER BARU DI WILAYAH KABUPATEN PURWOREJO JAWA TENGAH - Reizano Amri Rasyid; Rachma Rizqina Mardhotillah (STIE Mahardhika, 2021)
The smooth supply of broken stone will greatly affect and even determine the speed and accuracy of the completion of a project. The availability of large stones or blondos as raw material to produce broken stones must be guaranteed availability, for this reason it is very important to have a quarry or land containing blondos to maintain the continuity of raw material supply for the stone crusher business. Purworejo Regency has potential in terms of sand and stone mining. Most of the land consists of rock with a percentage of approximately 60% of the total area of Purworejo Regency. The type of raw material that is owned is andesite with a deposit of mining rock which can be exploited for mining for more than 20 years. Because of that potential, it is very important for PT. X to conduct a strategy analysis before constructing a new stone crusher unit. An appropriate business development strategy is needed. The purpose of this research is to create a business development strategy of PT.X by using the SWOT and TOPSIS methods. Based on the alternatives of the SWOT matrix obtained 8 strategies to develop the company and selected strategic priorities with TOPSIS found that market opportunities are very wide open and immediately expand the marketing network with a maximum value of 1.